Digitalization/Digital Transformation - Jörissen, Benjamin (Springer International Publishing, 2023)
From the perspective of the Antropocene, digitalization appears as a complex phenomenon. It consumes material and energy and produces toxic waste, while at the same time providing spaces and networks for change, serving as an informational, communicational, social, and cultural infrastructure that drives globally networked activism and policy-oriented discourses. This article discusses the need to move away from ‘solutionist’ (Morozov) approaches to resilience-oriented strategies that promote responsive, responsible, and empowering approaches to digitalization.
CRIS-Team Scopus Importer:2024-12-16